THE ORIGINS OF INDONESIAN EFL TEACHERS’ IDEOLOGICAL BELIEFS ABOUT ENGLISH AND ELT - Dery Tria Agustin (Universitas Wiralodra, 2023)
The last three decades or so have seen a proliferation of studies into second language (L2) teachers’ cognition, encompassing their thinking, knowledge, and belief. However, studies are lacking into the origins (or sources) of L2 teachers’ beliefs especially ideological beliefs. This paper reports a subset of findings from a study investigating the beliefs and classroom practices of secondary school EFL teachers in Indonesia. Aiming to reveal ideological beliefs about English and ELT held by the teachers and the perceived origins of such beliefs, the paper draws on data obtained from a total of 16 interviews. Data analysis revealed that the teachers held beliefs that reflect several categories of English language ideologies prevalent in the ELT setting. These ideological beliefs were perceived to originate from several factors such as schoolteacher’s talk about English, schoolteacher’s classroom practice, undergraduate education, graduate education, fellow teachers, colleagues in an English teacher forum, and textbooks used for teaching. The paper concludes with implications for English teacher education programs and suggestions for future research